Exploring the Factors on Student Satisfaction with Digital Payments in Higher Education - Saksono, Lalang (Pascasarjana UM, 2023)
The present study sought to elucidate the determinants of student satisfaction in relation to the adoption of digital payment systems in universities located in Central Java. The methodological approach employed was a quantitative analysis, utilizing linear regression for statistical evaluation. Our findings indicate that perceived usefulness exerts a positive and significant influence on student satisfaction when utilizing digital payments, as per the Technology Acceptance Model (TAM) approach, across various Central Java universities. However, perceived ease of use did not demonstrate a significant impact on student satisfaction within the same context. Interestingly, trust was found to have a positive and significant impact on student satisfaction regarding the usage of digital payments as per the TAM approach. Conversely, perceived security and risk factors were not found to significantly influence student satisfaction in the use of digital payments, in accordance with the TAM perspective. Taken together, perceived usefulness, perceived ease of use, trust, and perceived security and risk factors were found to exert a collective influence on student satisfaction in the context of digital payment usage.